UJI PERFORMA DAN ANALISA MESIN DLE-170 DENGAN VARIASI UKURAN PROPELLER - Hartono Danki (Institut Sains dan Teknologi Nasional, 2021)
The need for the use of engines that meet the criteria based on performance is a must in order to obtain the desired capabilities. In order to know the value of the performance of the machine product, sometimes testing is required. This test uses the DLE-170 engine by reading and analyzing parameters that serve to determine the torque, power, specific fuel consumption and efficiency of the engine. From the test results obtained the maximum power generated from the 32x10 propeller is 13,446 KW, while the maximum power generated from the 32x12 propeller is 11,034 KW. Specific fuel consumption (sfc) at 5000 RPM using a 32x10 propeller is 0.001066 kg/HP Hour, when using a 32x12 propeller at 5000 RPM the sfc value is 0.001223 kg/HP Hour. With the fuel efficiency produced by the 32x10 propeller has an average value of 17.061%, it can be said that the value of the test results using the 32x10 propeller is better than the 32x12 propeller.